The Influence of Leadership, Work Motivation and Compensation on the Performance of Employees of PT. Java-Bali Plantation Head Office in Surabaya - Martin Zebua; Rismawati Sitepu; Ilham; Emmywati; Noneng R S; Bambang Sri Wibowo (Journal of Islamic Economics Perspectives, 2021)
This study aims to examine and determine the relationship between leadership, motivation, and compensation for employee performance at PT. Generation of Java-Bali Headquarters in Surabaya. With the results of the study as follows: 1. Based on the data in the table above, the calculated t value of 3,876. Because the value of t count <t table (1.66023> 3.876) and the probability value of significance (0.00 <0.05) then H0 is rejected and Ha is accepted. This means that leadership partially has a significant effect on the performance of PT. Surabaya Java-Bali generation. 2. Based on the t table of 0.291. So that t count <t table (1.66023 <4.976) and the value of the probability of significance (0.00 <0.05) then Ho is rejected and Ha is accepted. This means that work motivation partially has a significant effect on the performance of PT. Surabaya Java-Bali generation. 3. Based on t table of 0.291 So that t arithmetic <t table (1.66023 <2.972) and the probability value of significance (0.00 <0.05) then Ho is rejected and Ha is accepted. This means that partial compensation has a significant effect on the performance of PT. Surabaya Java-Bali generation. 4.Based on the f table of 2.81. B ecause the value of f arithmetic> f table (35,669> 2.81) then Ho is rejected and Ha is accepted, which means. L eadership, work motivation, and compensation simultaneously have a significant effect on the performance of the employees of PT. Surabaya Java-Bali generation.